Anatomies of narrative criticism: the past, present, and futures of the Fourth Gospel as literature - Thatcher, Tom (Resources for biblical study, 2008)
Anatomies of the Fourth Gospel : past, present, and future probes / Tom Thatcher -- Hermeneutical reflections at twenty-five years -- Symbolism and history in John's account of Jesus' death / R. Alan Culpepper -- Building skyscrapers on toothpicks : the literary-critical challenge to historical criticism / Adele Reinhartz -- There and back again : Johannine history on the other side of literary criticism / Colleen M. Conway -- From one dialogue to another : Johannine polyvalence from origins to receptions / Paul N. Anderson -- Intratextuality and intertextuality in the Gospel of John / Jean Zumstein -- John is dead; long live John! / Robert Kysar -- Anatomical probes -- Magnificent but flawed : the breaking of form in the Fourth Gospel / Mark Stibbe -- The word of bare life : workings of death and dream in the Fourth Gospel / Tat-siong Benny Liew -- Resurrection dysfunction, or one hundred years of cinematic attempts at raising a stiff (john 11:1-46) / Jeffrey L. Staley -- Symbolic communication between John and his reader : the garden symbolism in John 19-20 / Ruben Zimmermann -- John 21 and the Johannine story / Francis J. Moloney -- Afterword: Things not written in this book / Stephen D. Moore